Indicators and Variables for Measuring Farmers’ Resilience: Efforts to Promote Aceh Coconut Business Sustainability - Henny Sulistyorini; Sumardjo; Anna Fatchiya; Ninuk Purnaningsih (Jurnal Penyuluhan Pertanian, 2025)
A resilient and sustainable society is goal 11 of the Sustainable Development Goals (SDG's) to be achieved by 2030. A resilient society is able to withstand the threat of adverse external environmental changes. Currently, coconut plantations in Aceh are threatened by declining planted area, unproductive crops, minimal access to technology, and weak function of farmer institutions. On the other hand, coconut is a strategic commodity for the Acehnese people. These threats can be overcome if farmers have a high level of resilience. However, currently there are no indicators and variables to measure this. This research strategically addresses this gap because it aims to formulate quantitative resilience indicators and variables based on a survey of 277 coconut farmers. The research was conducted in Aceh Besar, Bireuen, and Simeulue district from May to August 2024. Data analysis used Structural Equation Model (SEM) with PLS 4.0. The research found valid and reliable indicators for measuring farmer resilience, including the capacity to implement livelihood strategies, social integration, and coconut plantation conservation efforts. Farmer resilience significantly influenced by implementation of agricultural extension, the role of extension workers, social capital, and the role of chief of farmer group. It was concluded that strengthening farmer resilience was achieved through improving extension with methods and materials tailored to farmer's needs, enhancing the role of extension workers as motivators and facilitators of resource access, developing social capital through building farmer trust and network, and strengthening the leadership and motivators role of chief of the farmer group in coconut development.